Facile synthesis of synergistic Pt/(Co-N)@C composites as alternative oxygen-reduction electrode of PEMFCs with attractive activity and durability. (15th July 2020) - Hu, Bin; Deng, Xiang; Zhou, Liusheng; Dai, Jie; Yang, Guangming; Tan, Wenyi; Zhou, Wei; Shao, Zongping
Abstract: The development of cost-effective electrocatalyst with high activity and durability for oxygen reduction reaction (ORR) in acidic condition is a key step towards the wide-spread application of proton exchange membrane fuel cells (PEMFCs), while the high cost of benchmark Pt/C is one of the main inhibiting factors. Here, we report a new composite catalyst by adopting electrocatalytically active Co, N-modified carbon prepared from a cost-effective method with mass production capability. The as-prepared Pt/(Co-N)@C catalyst shows a favourable mass activity of 0.227 A mgPt −1 as well as superior durability with only 15.4% of performance loss after 30, 000 cycles, making it a highly promising ORR electrocatalyst for practical PEMFCs.